National best practice guidelines for anaphylaxis prevention and management in Australian schools - Merryn J. Netting, PhD; Briony Tyquin, MNurs; Wendy Freeman, MBBS; Katie Frith, MBBS; Heather Roberts, BHlthSc Hons; Maria Said, RN; Preeti Joshi, PhD; Sandra Vale, PhD (Journal of Allergy and Clinical Immunology: Global)
Background: Anaphylaxis prevention and management in the school setting is an important health and safety issue as the rates of food allergy in children continue to increase. Objective: We describe the development and review of the Australian National Allergy Council best practice guidelines for anaphylaxis prevention and management in schools. Methods: Developed in consultation with key stakeholders in health and education settings, the best practice guidelines incorporate 7 key recommendations for anaphylaxis prevention and management: an allergy aware approach; anaphylaxis management policy and plans; allergy documentation; emergency response; staff training; community and student education; and postincident management and incident reporting. Results: An audit of Australian state and territory education department anaphylaxis guidelines, policies, and procedures indicates that most align with best practice recommendations. Conclusions: Ongoing reporting and evaluation of anaphylaxis incidents across all 8 jurisdictions in Australia helps us evaluate the implementation of these measures in the school setting.